A dimensão institucional da magia no neopentecostalismo: o papel decisório do poder mágico como atrativo a adesão religiosa na Igreja Universal do Reino de Deus - Leite, Lucas Farias de Vasconcelos (2010)
This paper describes the rapid growth of neo-pentecostal movement, especially the Universal Church of the Kingdom of God, in the current context of "disenchantment of the world." Paradoxically like imagine some time ago, religious movements have grown increasingly, and in the case of the Universal Church of the Kingdom of God, just as in any neo-pentecostalism, we believe that this increase is related to configuration of their rites. The use of magic rituals such religious denomination occurs consistently with the appropriation and reinterpretation of elements of Brazilian religiosity in the modern world´s context. Both the ballast cultural practice of magic between the company for over five centuries of history, as the dip in mysticism in search of meaning in the face of modern afflictions. And more. According Marcel Mauss, the magic is "by definition, an object of belief,"everybody whouses it believes in its effectiveness. The prosperity as spectrum underlying the rites, embodies consumption´s power and efficiency that only in magic, it is possible to mobilize energies that become hostage the sacred action.